An overview of the pathogenesis, etiologies, and treatment of myocarditis - Danna, Colleen, author (Colorado State University. Libraries, 2024)
Myocarditis is a rare heart condition that has an extensive range of causes, various forms of disease development, and a diverse clinical presentation across age groups. In recent years, there has been a global rise in myocarditis incidences, prompting a more in-depth investigation of this condition by researchers across public and private institutions. Despite these research efforts, there is still a wealth of information yet to be uncovered. It is the intent of this thesis to provide a comprehensive overview of the condition as a whole, with discussion focused on the primary means of diagnostic testing and the occurrence of myocarditis worldwide. Special attention is also given to the categorization of the various subtypes based upon their respective etiologies, which overlap at times. Following this, there is discussion of the biological mechanisms by which myocarditis develops, along with the current treatment options available for patients. This literature review was achieved via compiling information across numerous peer-reviewed journal articles and clinical case studies.
University Honors Program.
Keywords: myocarditis; pathogenesis; etiology; subtypes; epidemiology; diagnosis